Internet banking: a review (2002–2016). Issue 3 (3rd July 2018) - Keskar, Mugdha Y.; Pandey, Neeraj
Abstract: This paper presents an exhaustive review of literature on the current developments in internet banking. It provides an overview of the changes as well as the ongoing research on internet banking. To identify relevant works, research databases were searched using 11 keywords. Only research papers on internet banking published in the last 15 years (2002–2016) were selected. The selected articles were further refined on the basis of country of origin, journal type, and research methods used for data analysis. Finally, 51 papers were selected on the basis of specific inclusion criteria for further analysis. These papers were grouped by research themes, and customer satisfaction with internet banking was identified as the most common theme.